Challenges and Latest Developments in Diffusion Bonding of High-Magnesium Aluminium Alloy (Al-5056/Al-5A06) to Stainless Steels - Amir A. Shirzadi; Chengcong Zhang; Muhammad Zeeshan Mughal; Peiyun Xia (Metals, 2022)
The aim of this work was to investigate the challenges associated with bonding Al-Mg alloys and develop a new method for bonding these alloys to steels. During an extensive R&D project, over 80 attempts, using 11 methods, were made to bond Al-6 wt.% Mg alloy (Al-5056/Al-5A06) to two types of stainless steels (heat-resistant 1Cr18Ni9Ti and conventional 316). Wide ranges of temperature (500 °C to 580 °C), pressure (0.5 MPa to 10 MPa) and time (1 min to 2 h) were used when direct diffusion bonding of these alloys. Then, effects of using various interlayers and brazing foils were investigated. The interlayers used in this work were gallium, pure titanium, copper and aluminium foils, aluminium 6061 alloy sheets, aluminium-silicon brazing foils, zinc and zinc alloy foils as well as an active brazing foil (known as Incusil-ABA containing silver, copper, indium and titanium). Several complex and multi-stage processes, using up to 3 different interlayers in the same joint, were also developed and assessed. Examination and assessment of the bonded samples, including failed attempts, paved the way of developing new methods for bonding these dissimilar materials. A number of samples with tensile strengths from 200 MPa to 226 MPa were made by using complex combinations of 2 or 3 interlayers and triple-stage bonding cycles. The highest recorded bond strength was 226 MPa in the as-bonded condition. This value is above the measured yield strength (134 MPa) and about 93% of the measured ultimate strength (243 MPa) of the parent Al-Mg alloy after it was subjected to the same bonding cycle. Since the use of complex processes was not feasible for bonding large components, a simpler and more practical bonding cycle was also developed in the project. Using the simpler process, joints with tensile strengths around 90 MPa could be made. This article also sheds light on the difficulties associated with brazing and soldering aluminium alloys with a high magnesium content.